Improving the efficiency of individually randomized clinical trials by staggering the introduction of the intervention. (17th September 2018) - Hooper, Richard; Knowles, Charles
Abstract : In cluster randomized trials, the introduction of the intervention can be staggered in different clusters, leading to a stepped wedge design. This strategy can lead to gains in efficiency, which might also translate to the context of individually randomized trials, though this has been relatively unexplored. Here, we present one illustrative example. We consider trials in which participants start in a control condition such as routine care and can cross over at any stage to the active intervention. We make the assumption that the effect of the intervention is the same however long the delay before a participant crosses over to the intervention condition. We consider designs for a trial with three repeated assessments, including a baseline, and show that a three‐sequence design with staggered introduction of the intervention in two of the sequences estimates the treatment effect after one period more efficiently than a parallel groups design.